Performance evaluation and life cycle analysis of RES-hydrogen hybrid energy system for office building. (3rd February 2021) - Peppas, Antonis; Kollias, Konstantinos; Politis, Antonis; Karalis, Lampros; Taxiarchou, Maria; Paspaliaris, Ioannis
Abstract: A self-sustained, zero-CO2 emission RES-H2 Hybrid Energy System (HES) was developed at Lavrion Technological & Cultural Park (Attica, Greece) to cover electric power, heating/cooling loads (tri-generation) of an office building located in its premises. The primary energy is harvested from RES and directly applied to cover contingent loads, whereas the excess energy is converted to hydrogen to be used as energy storage system and thus as a green fuel to cover the building heating needs through direct combustion or to produce combined heating and electricity by means of fuel cells. In this study, the performance of the functional RES-H2 HES is evaluated as well as its impact by applying the methodology of Life Cycle Assessment. HES resulted in the reduction of Global Warming Potential, Acidification Potential and Photochemical Oxidant Formation by 40%, 42% and 35%, respectively, compared to the exclusive use of Greek energy grid mix for electricity. Highlights: Life Cycle Assessment of a hybrid RES-H2 Hybrid Energy System developed in Greece. Hybrid Energy System reduced GWP by 40%, compared to the use of GR-energy grid mix. AP is decreased on Hybrid Energy System by 42%, compared to the GR-energy grid mix. POF of Hybrid Energy System was 35% less compared to the use of GR-energy grid mix. Environmental impact of PVs was 5 times higher, compared to WTs.